2014
DOI: 10.1039/c4cc02137a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of asymmetric Ag–organosilica hybrid nanoparticles with tunable morphologies and optical properties

Abstract: This study reports a simple and novel wet-chemical method for synthesizing asymmetric Ag-organosilica hybrid nanoparticles with finely-tuned morphologies and optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…25,27,28 In addition, from both curves, the -C-O-Cstretching vibration at 1103 cm À1 from mPEG block were observed. 39 Based on these results, it is concluded that the ester bond still existed and the Ag NWs were wrapped with the PVP chain with mPEG tails on the surface.…”
Section: Synthesis and Characterization Of Ag Nwsmentioning
confidence: 91%
“…25,27,28 In addition, from both curves, the -C-O-Cstretching vibration at 1103 cm À1 from mPEG block were observed. 39 Based on these results, it is concluded that the ester bond still existed and the Ag NWs were wrapped with the PVP chain with mPEG tails on the surface.…”
Section: Synthesis and Characterization Of Ag Nwsmentioning
confidence: 91%
“…In comparison with the other noble metals, silver has gained less interest in the fabrication of Janus particles. Some silver-gold bimetal or silver-sillica Janus nanoparticles have been prepare by depositing growth on the metal seeds [ 27 , 28 , 29 , 30 ]. Chen et al [ 27 ] had compared a Janus Au@Ag nanoparitlces to their Au@Ag and Ag@Au core-shell counterparts, and found that the Janus nanoparticles exhibited enhanced electrocatalytic activity in oxygen reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Janus nanostructures have emerged as a new family of colloidal structured materials, and attracted the attention of many researchers owing to their potential applications in many fields such as drug delivery, imaging probes, electronic devices, and catalysis . Janus nanostructures have many advantages compared with other complex nanoparticles, such as combing individual components together, even incompatible acidic and basic groups, and retaining their intrinsic properties . Now, many methods for preparing Janus nanostructures have been reported, including one‐step synthesis, surface chemical‐selective modification, self‐assembly, and others .…”
Section: Methodsmentioning
confidence: 99%